CIRA: a synopsis of activity, September 1980 - December 1981 - Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1982)
This first "mid-year" report from the Cooperative Institute for in the Atmosphere (CIRA) is intended to communicate scientific results and information about current activities to NOAA and CSU scientists, students and staff as well as other interested parties. Falling as it does at a report time after the first full year of CIRA operations, it thus becomes the first CIRA summary report to carry scientific information.
February 1982.
Keywords: Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.); Atmosphere -- Research; Meteorology -- Research